Acupuncture and Burning Mouth Syndrome: A Pilot Study. Issue 8 (21st January 2013) - Sardella, Andrea; Lodi, Giovanni; Tarozzi, Marco; Varoni, Elena; Franchini, Roberto; Carrassi, Antonio
Abstract Burning mouth syndrome (BMS) is a chronic condition most common in middle‐aged and elderly women, with prevalence rates in the general population ranging from 0.5% to 5%. Defined by the International Headache Society as "an intraoral burning sensation for which no medical or dental cause can be found, " BMS is considered a form of neuropathic pain. The management of BMS remains unsatisfactory. In this pilot study, we investigated the use of acupuncture in a small group of BMS patients. The study group, after 4 refusals, was composed of 10 BMS patients (9 females and 1 male; mean age, 65.2 years; range, from 48 to 80 years; mean duration of BMS, 2.6 years; SD ± 0.8 years). Oral pain/burning sensation (primary outcome) was measured using a visual analogue scale (VAS). Health‐related quality of life (secondary outcome) was measured using the 36‐item Short‐Form Health Survey (SF‐36). Acupuncture treatment lasted 8 weeks and consisted of 20 sessions. Patients reported a mean reduction in pain of 0.99 points on the VAS (max 2.1–min 0.1), which, although slight, was statistically significant (Wilcoxon test P < 0.009). No significant improvement in the overall score for quality of life was observed, although subjects receiving acupuncture treatment seemed better able cope with their oral symptoms.